Organizing Pneumonia by Paragonimiasis and Coexistent Aspergilloma Manifested as a Pulmonary Irregular Nodule. (2011) - Lee, In Jae; Seo, Jinwon; Kim, Dong Gyu
Abstract : Organizing pneumonia by paragonimiasis and coexistent aspergilloma as a pulmonary nodule is a rare case of lung disease. Its radiographic or CT feature has not been described before in the radiologic literature. We present organizing pneumonia by paragonimiasis and coexistent aspergilloma manifested as a pulmonary irregular nodule on CT.